Peningkatan Hasil Belajar Siswa Pada Pembelajaran Tematik Terpadu Menggunakan Pendekatan Saintifik - Daulay, Nurmawati; Amerta, Sri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2019)
The purpose of this study was to describe the increase in student learning outcomes in integrated thematic learning using Scientific approach in class I SD Negeri 12 Bukik Cangang. The research subjects were teachers (practitioners) and 29 students. The research location is SD Negeri I SD Negeri 12 Bukik Cangang. The results showed an increase in: a) RPP observation of the first cycle was 76,11% (C), the second cycle was 94,44% (A); b) Observation aspect of the first cycle teacher is 79,5% (C), the second cycle is 93,75% (A); c) Observation aspects of the student's first cycle is 81,06%  (B) and the second cycle is 90,62% (A); d) learning outcomes in the first cycle are 71,58 (C) and the second cycle is 82,24 (B).